One-year cardiac morphological and functional evolution following permanent pacemaker implantation in right ventricular septal position in chagasic patients - Silva Júnior,Otaviano da (2012)
INTRODUCTION: The septal position is an alternative site for cardiac pacing (CP) that is potentially less harmful to cardiac function. METHODS: Patients with Chagas disease without heart failure submitted to permanent pacemaker (PP) implantation at the Clinics Hospital of the Triângulo Mineiro Federal University (UFTM), were selected from February 2009 to February 2010. The parameters analyzed were ventricular remodeling, the degree of electromechanical dyssynchrony (DEM), exercise time and VO2 max during exercise testing (ET) and functional class (NYHA). Echocardiography was performed 24 to 48h following implantation and after one year follow-up. The patients were submitted to ET one month postprocedure and at the end of one year. RESULTS: Thirty patients were included. Patient mean age was 59±13 years-old. Indication for PP implantation was complete atrioventricular (AV) block in 22 (73.3%) patients and 2nd degree AV block in the other eight (26.7%). All patients were in NYHA I and no changes occurred in the ET parameters. No variations were detected in echocardiographic remodeling measurements. Intraventricular dyssynchrony was observed in 46.6% of cases and interventricular dyssynchrony in 33.3% of patients after one year. CONCLUSIONS: The findings of this work suggest that there is not significant morphological and functional cardiac change following pacemaker implantation in septal position in chagasic patients with normal left ventricular function after one year follow-up. Thus, patients may remain asymptomatic, presenting maintenance of functional capacity and no left ventricular remodeling.